PENINGKATKAN KUALITAS PELAYANAN PEMBUATAN IZIN MENDIRIKAN BANGUNAN (IMB) RUMAH TINGGAL MELALUI PROFESIONALISME KERJA DI BADAN PELAYANAN PENANAMAN MODAL DAN PERIJINAN TERPADU (BPPMPT) KOTA TANGERANG - Effendi Effendi; Cecep Sudrajat (JMB : Jurnal Manajemen dan Bisnis, 2017)
This study aims to the extent to which the work professionalism ofemployees can improve the quality of service in building a BuildingPermit (IMB) at the Tangerang City One Stop Investment Service. Thehypothesis proposed is: "There is a Positive Role of Employee WorkProfessionalism in Improving the Quality of Service for BuildingConstruction Permits (IMB) in Tangerang City BPMPTSP".Based on theresults of the study, it is known that there is a positive and significantrole of work professionalism in improving the quality of residential IMBservices.The higher the value of work professionalism, the higher thequality of service for the IMB of the Residence in Tangerang CityBPMPTSP.The results of this study inform that the variableprofessionalism of work is an important factor in improving the qualityof service for making residential building permits (IMB).